ANALISIS PEMASARAN KEMENYAN (Styrax spp.) (Studi Kasus : Kec. Pollung, Kab. Humbang Hasundutan) - Bobby Raya Simanjuntak; yunus afifuddin; Ridwanti Batubara (Program studi Kehutanan USU, 2012)
Forest incense owned District Pollung potential managed and marketed for economic improvement. It aims to analyze the marketing groove incense, knowing economic value from incense and determining marketing strategies in District Pollung, District Humbang Hasundutan. The method applied is purposive sampling with total sample of 40 (forty) respondents. Data collected through observation and analysis problems with interviews using questionnaires to farmers and entrepreneurs incense. Overall data, both primary and secondary, then tabulated according to need. The value of highest profit margins obtained farmers on market II, amounting to 72.22% and the smallest profit margins in the village collecting 10% on market I. The largest average income is equal Rp.2.829.400/ family leader/month in Pandumaan. While the smallest income of Huta Paung Utara Rp.1.024.600/family leader/month. Strategic marketing priorities incense is formed farmer groups and cooperatives at the village, the supervision of the marketing system incense, incense sustainable management, human resource and the use of incense superior seedlings. Keywords: incense, marketing, economic value and marketing strategy